The doctoral research abstracts. Vol:4 2013 / Institute of Graduate Studies, UiTM - Universiti Teknologi MARA, Institute of Graduates Studies (Institute of Graduate Studies, 2013)
Foreword: The fourth issue of The Doctoral Research Abstracts captures the novelty of 24 PhD doctorates from 12 of the university’s 25 faculties. These abstracts ranged from the discipline of science and technology, business and administration to social science and humanities. The publication epitomizes knowledge par excellence and marks UiTM acknowledgement and tribute to the graduands whose achievements we proudly celebrate. This convocation should not be regarded as the end of your highest scholarly achievement and contribution to the body of knowledge but rather as the beginning of embarking into more innovative research from knowledge gained during this academic journey, for the community and country. As alumni of UiTM, we hold you dear to our hearts. The relationship that was once between a student and supervisor has now matured into comrades, forging and exploring together beyond the frontier of knowledge. We wish you all the best in your endeavour and may I offer my congratulations to all the graduands. ‘UiTM sentiasa dihati ku’